‘DAGUSIBU' (GET, USE, SAVE, AND DISPOSE) DRUG MANAGEMENT COUNCELLING IN PENGALANGAN VILLAGE, MENGANTI DISTRICT, GRESIK REGENCY - Ibaidah, Puji; Az Zahra, Nadhifa; Sakina, Antya Putri; Hadi, Vivia Inayah; Azizah, Putri Nur; Ayudya, Fidela Putri; Nusantara, Rizal Harjuna Guntur; Zahra, Alisa; Kiuk, Farel Jevons (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Self-medication behaviors of the society kept increasing as years passed, including for the residents of Desa Pengalangan, Kecamatan Menganti, Kabupaten Gresik. Over-the-counter medicines, the ones that can be obtained without a prescription, have been a prior solution to relieve the symptoms of various diseases. Unfortunately, the consumption of these medicines is not accompanied by proficient knowledge of how to manage medicines properly. Consequently, the health of the community and environment are negatively affected. Therefore, it is considered crucial to educate society as a form of approach made for promoting public health and preventing the irrational usage of medicines. Socialization of the ‘DAGUSIBU' (dapatkan, gunakan, simpan, dan buang) [eng: get, use, store, and dispose] of medicines through a session of interactive mini-lecture and simulation, has been chosen to be the proper modality to deliver such information about managing medicines. About 21 health cadres of Desa Pengalangan are involved in this program, fulfilling the pretests and post-tests as instruments to determine the level of knowledge of the society about medicines. Based on the result of this program, it is noted that an average of 80.9% participants' level of knowledge increases after socialization. Highest increase in the level of knowledge is reported in the topics ‘Golongan obat' [eng: drug's classes] (85,7%) and ‘DAGUSIBU obat' (85,7%), while the topic ‘Penggunaan antibiotik' [eng: antibiotic usage] (71,4%) becomes the topic with the least increase in the level of knowledge. Though these findings seem in line with the previous studies, innovations are required to optimize the increase of society's level of knowledge in managing medicines.